(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Pampean region is a fertile and extensive plain of Argentina. It has an extension of 613,532 km2 located within the temperate region, being also adjacent to the Atlantic Ocean. The latter generates low daily and annual thermal amplitudes than in other regions in similar latitudes. In addition, the region is characterized by the occurrence of long periods of floods and drought, which affect the availability of water resources (Aliaga et al., 2017). The Buenos Aires Province is especially characterized by the presence of aeolian landscapes that, even though they were developed in the past, they are currently being reactivated by agricultural activities. The antecedents indicate different dune morphologies within the province territory, mainly associated with sediment availability and wind direction (Iriondo and Kröhling, 1995; Isla et al., 2010; Zárate and Tripaldi 2012). The focus of this work is the detection, delimitation and characterization of a parabolic dune field located in the Middle West of the Buenos Aires Province (Fig. 1) for which no precedent has been found. Likewise, we also establish the relationship between the parabolic dunes and the distribution and evolution of the interdune shallow lakes associated with them. Through the generation of a Digital Elevation Model (DEM) from Shuttle Radar Topography Mission (SRTM) images, a field with 254 parabolic dunes that covers 20,200 km2 was detected (Fig. 1). It is located between 120 and 90 m above mean sea level, with SW-NE general orientation; widths between 2 and 5 km, and heights between 2 and 6 m. The Vertical Distance to Channel Network (VDCN) tool of the SAGA GIS 2.1.2 software was also employed (Fig. 3) and, additionally, an automatic unsupervised classification using ArcGIS 10.1 was carried out in order to discriminate the dunes from the surrounding plain. Grain size analysis were carried out in both dune and interdune areas. The analysis was performed employing a Mastersizer 2000 Laser Particle Analyzer, whose results were represented with the GRADISTAT v8 software. The results demonstrate clear differences between the interdune areas, having very fine materials, with respect to those obtained within the dune area, which varied depending on the sector and the depth of the sample, establishing differences in the various dune sectors. For example, an increase in finer materials in depth. Also revealed that they are fine sand dunes, but the bimodal curve obtained with fine materials suggests that its sediments respond to different climatic periods. The progressive increase of fine material inside the dune shows that there is a material redistribution. Simultaneously with the sampling, a flight with an unmanned aerial vehicle (UAV) was made, that allowed generating a set of videos and 360º panoramic photographs, later used in the generation of orthomosaics, dense point cloud and a three-dimensional model (Fig. 6) using the SFM (Structure From Motion) method (Genchi et al., 2015). The method is based on sequential image acquisition, with a high overlap degree, and founded in the correlation of points identified in different images (Fernández and Gutiérrez, 2016). The images were optimized (USGS, 2016) obtaining a higher accuracy in the photograph parameters by correcting the distortions caused by the camera lens. Besides the method helps to improve the general model, whose scene geometry, camera location and orientation of the photographs were taken automatically but derived from the appropriate superposition (> 60 %). According to its morphology, the dunes were categorized into three classes (Table 1), being the symmetric dunes the most common, followed by the asymmetric dunes and, finally, those of lateral coalescence that, despite being inferior in quantity, possess greater spatial development, that is, have longer crestal lengths (Fig. 7). Bordering the margins of the dune field to the north, east and south we observed the typical longitudinal dunes characteristic of this Pampean region sector. According to Bagnold (1941), it is possible that some simple semilunar forms are deformed in longitudinal features when moving in areas with variable wind directions. The results demonstrate that there are 254 crests distributed in the area, with a density of 0.01 dunes/ km2, many of them are segmented due to natural process through the presence of small shallow lakes and temporary depressions whose approximate depth is 1 m (Fig. 4 and 5), but also increased by the removal of soils as a result of agricultural activity. The shallow lakes disposition allows inferring that, in presence of abundant rainfall; they can be connected and/or overflowed, flooding the surrounding areas. The location of these dunes is crucial in the spatial surface runoff configuration and, in consequence, this sandy landscape has an important role in the spatial configuration of the area generating risk conditions to both the local population and agricultural production.